Unbonded CFRP strengthening method for buckling control of steel members. (30th April 2020) - Yoresta, Fengky Satria; Maruta, Ryotaro; Mieda, Genki; Matsumoto, Yukihiro
Highlights: Concept of unbonded CFRP strengthening method for axial compression steel members. Unbonded CFRP delays buckling and increases the axial capacity of steel members. VaRTM technique is adopted in CFRP molding. Equivalent slenderness ratio is proposed in strength evaluation for design. Abstract: This paper proposed a concept of unbonded CFRP strengthening method for buckling control of axial compression steel members. Totally eight steel bar specimens, with slenderness ratio of 70 and 95, were tested for initial investigation purpose. The requirements for CFRP were derived from analytical study. A technique of Vacuum-assisted Resin Transfer Molding (VaRTM) was adopted to mold the CFRP to obtain zero clearance between CFRP and steel. Experimental results showed that unbonded CFRP strengthening delayed buckling and increased the axial capacity of steel members. A change in curvature was also confirmed for all strengthened members without any crushing on CFRP.